Overexpression of a Vesicle Trafficking Gene, OsRab7, Enhances Salt Tolerance in Rice - Xiaojue Peng; Xia Ding; Tianfang Chang; Zhoulong Wang; Rong Liu; Xin Zeng; Yaohui Cai; Youlin Zhu (The Scientific World Journal)
High soils salinity is a main factor affecting agricultural production. Studying the function of salt-tolerance-related genes is essential to enhance crop tolerance to stress. Rab7 is a small GTP-binding protein that is distributed widely among eukaryotes. Endocytic trafficking mediated by Rab7 plays an important role in animal and yeast cells, but the current understanding of Rab7 in plants is still very limited. Herein, we isolated a vesicle trafficking gene, OsRab7, from rice. Transgenic rice over-expressing OsRab7 exhibited enhanced seedling growth and increased proline content under salt-treated conditions. Moreover, an increased number of vesicles was observed in the root tip of OsRab7 transgenic rice. The OsRab7 over-expression plants showed enhanced tolerance to salt stress, suggesting that vacuolar trafficking is important for salt tolerance in plants.